Statistical Cloud-to-Ground Lightning Data and Its Implementation for 33kV Overhead Line in Peninsular Malaysia - Hatta N.M.; Abdullah N.; Osman M.; Mohamad A. (Institute of Electrical and Electronics Engineers Inc., 2024)
This paper provides an overview of the cloud-to-ground lightning events recorded by a lightning detection system (LDS) network in Peninsular Malaysia between 2018 and 2022. The existing LDS comprises five sensors, a central processor, a database management system, and real-time terminals for displaying lightning activity. In 2017, after fourteen years of operation, the network underwent an upgrade to the most recent system offered by Vaisala Inc., USA. This upgrade introduced the latest sensor generation technology, LDSN enhancements, and improvements in network performance. Additionally, the paper will discuss the utilization of collected cloud-to-cloud lightning data to enhance the reliability of distribution overhead lines. 2023 IEEE.